Quit Smoking Clinic Attendees And Their Intentions To Quit Smoking: A Health Belief Perspective - Ooi, Swee Yaw (2019)
The Malaysian government has committed itself to reduce uptake in smoking and increase smoking cessation using a multiple approaches. One of the most significant media campaign undertaken by the government is the anti-smoking “Tak Nak!” campaign. This aggressive campaign based on fear provocation in the mainstream media and on-pack cigarette advertising is to drive smokers to seek for help in the Quit Smoking Clinics established nationwide. This research aimed at testing the Health Belief Model (HBM) to identify important variables that will have an influence on intentions to quit smoking. A total of three Quit Smoking Clinics in Kuala Lumpur city area were selected based on size of attendees and viability. From these three clinics a total of 133 respondents were selected using a purposive sampling approach. Correlations test between the independent HBM variables namely perceived susceptibility, perceived benefits, perceived barriers, cues to action, general health orientation, self-efficacy, perceived severity and quit intentions (dependent variable) showed that perceived susceptibility, cues to action and self-efficacy were positively and significantly correlated to the quit iii intentions. Based on the research outcome, quitting intention can be enhanced by emphasizing on anti-smoking fear campaign to signal the attendees to stop smoking because they will be highly susceptible to the danger. The research also shows that self-efficacy needs to be emphasized where the attendees should be trained to instill self-confidence in order to stop smoking. Besides, the research also shows that the there are no other barriers from quitting smoking such as transportation, time and others.